2020
DOI: 10.1039/c9fo02623a
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota modulation and effects on metabolic biomarkers by orange juice: a controlled clinical trial

Abstract: Regular consumption of 300 ml of orange juice d−1 for 60 days altered the intestinal microbiota, increasing Akkermansia and Lactobacillus, while Ruminococcus decreased. These changes were inversely correlated with metabolic biomarkers in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 43 publications
1
42
2
4
Order By: Relevance
“…To the best of our knowledge, this is the first study to assess insulin sensitivity in subjects consuming OJ utilizing an OGTT-derived index. Our results are in contrast to those of previous studies that reported improved insulin sensitivity in subjects consuming OJ when assessed by HOMA-IR [25,54,55]. It is possible that the improved [55] or unaffected [25] HOMA-IR observed in subjects consuming OJ in previous studies may relate to the amount of OJ consumed.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…To the best of our knowledge, this is the first study to assess insulin sensitivity in subjects consuming OJ utilizing an OGTT-derived index. Our results are in contrast to those of previous studies that reported improved insulin sensitivity in subjects consuming OJ when assessed by HOMA-IR [25,54,55]. It is possible that the improved [55] or unaffected [25] HOMA-IR observed in subjects consuming OJ in previous studies may relate to the amount of OJ consumed.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are in contrast to those of previous studies that reported improved insulin sensitivity in subjects consuming OJ when assessed by HOMA-IR [25,54,55]. It is possible that the improved [55] or unaffected [25] HOMA-IR observed in subjects consuming OJ in previous studies may relate to the amount of OJ consumed. The subjects in our study consumed more than twice the amount of OJ as the subjects in these studies [25,55].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…and Ruminococcus spp. according to other authors [168], suggesting that orange juice showed a prebiotic effect, modulating the intestinal microbiota by improving blood sugar and the lipid profile. In a recent review [169], it was highlighted how the beneficial effects of hesperidin on cardiovascular risk factors can be partly attributed to the modulation of the intestinal microbiota.…”
Section: Comorbiditiesmentioning
confidence: 59%